Bridging Borders with AI: Enhancing Global Cybersecurity Through Intelligent Threat Detection (International Journal of Scientific Research and Management (IJSRM), 2025)
With increasing global interconnectedness and digitization of the world, which is affecting everything from critical infrastructure to personal communication, cybersecurity has become a critical issue for humanity. A significant increase in the intelligence and the number of cyber incidents - that could be from state-sponsored agents or from various criminal groups - requires a fast and united global reaction. Old-fashioned security frameworks usually let down under the conditions of a large scale and complexity of modern cyber threats. In the current situation, AI is the leading entity capable of revolutionizing cybersecurity worldwide by clever threat detection systems. With the help of machine learning, natural language processing, and predictive analytics, AI-powered platforms can detect deviations, analyze the potential threat, and trigger immediate responses to a much greater extent than human analysts can. Moreover, cybersecurity is a borderless thing, hence due to the continuous nature of cybercrime, this necessitates cross-national collaboration—a process where AI can also be of help by providing common intelligence, matching defense protocols, and joint reactions. Firstly, the paper discusses the topic of the AI of raising global cybersecurity due to its smart threat detection capacity. This research outlines the various implementations, global cooperation models, and AI-assisted cybersecurity projects showhow AI incites not only operational efficiency but also international trust and interoperability. Secondly, it explores the challenges of ethics, data privacy, and the need for transparent algorithmic governance. It ends with the provisions for progressing AI integration in the global cybersecurity ecosphere. Hence, it illustrates the significance of AI as a means of bridging national borders to form a cyber-secure world for everyone.